EU solidarity at a time of gas crisis: Even with a will the way still looks difficult - Katja Yafimava (The Oxford Institute for Energy Studies, 2023)
Helped by anomalously warm winter temperatures, the EU appears increasingly likely to get through the current winter relatively unscathed. But next winter could be significantly more challenging if Russian gas supplies were to decrease further or stop altogether, especially if accompanied by rising China LNG demand, interruptions of other supplies, and cold winter temperatures. In this case, sharing of limited gas supplies across the EU could become a necessity. This paper analyses various solidarity (sharing) measures stipulated by the EU acquis and their impact on central and east Europe (Germany, Austria, Czechia, Slovakia, and Hungary), potentially the most affected sub-region. Specifically, it examines the SOS Regulation's solidarity obligation, which stipulates reduction of gas supply to all customers other than solidarity-protected customers in one Member State to enable another Member State, which declared an emergency and requested solidarity, to supply its solidarity-protected customers. This obligation has been amended by the Enhancing Solidarity Regulation and has been extended to supplies of critical gas volumes for electricity security of supply. The paper also examines a 15 per cent gas demand reduction requirement, introduced by the Gas Demand Reduction Regulation, which becomes mandatory in the event of a Union alert being triggered by the Council. This measure aims at spreading demand reduction more evenly across the EU.The paper argues that the EU solidarity measures would likely have only a limited impact on the gas supply situation in the central and east European sub-region, as infrastructure constraints would limit the volume of 'freed up' gas that could flow there from the other Member States. Nonetheless, the impact, particularly that of implementation of the SOS/Enhancing Solidarity Regulation solidarity obligation by central and east European Member States themselves (especially Germany, as a 'gate keeper' for LNG and Norwegian pipeline gas) as well as by the other Member States, would not be negligible. It would provide the safeguard of consumption by solidarity protected customers as well as volumes critical for electricity security of supply. Development of additional LNG import terminals would help but in the short-term (possibly until 2025) even with maximum assistance from the other Member States, Germany and other central and east European countries could find it difficult to cope with the consequences of any further significant reduction in Russian flows. Therefore, unless a recession triggers an even more significant gas demand reduction than is currently observed in Europe, there is a significant risk that rationing will be needed in winter 2023-24. Fortunately, there is time for the EU to prepare by adding more LNG import capacity, concluding additional solidarity agreements, and strengthening preventive action and emergency plans ahead of next winter.
Keywords: 330; alert; emergency; emergency plans; gas demand reduction; LNG; preventive action plans; Security of supply; solidarity; solidarity agreements; solidarity obligation